Neighboring group stabilization by sigma-holes - O'Hair, Richard A. J.; Williams, Craig M.; Clark, Timothy (Journal of Molecular Modeling, 2010)
We have used density-functional theory to investigate the neighboring-group stabilization of iodine, arsenic, and phosphorus-centered oxyanion moieties in species such as deprotonated 2-iodoxybenzoic acid (IBX) and its analogs. The magnitudes of different stabilizing effects and further candidates for analogous stabilization are analyzed.
Keywords: Density functional theory; sigma-Hole; IBA; IBS; IBX; 2-iodoxybenzoic